Role of diagnostic laparoscopy in chronic abdominal pain - Hussain, Sajid; Haideri, Safia (International Surgery Journal, 2019)
Background: Chronic abdominal pain is a common disorder both in general practice and in hospitals. Although patients with this type of pain may have undergone numerous diagnostic workups, including surgery, their pain remains a challenge to all known diagnostic and treatment methods. Laparoscopy can identify abnormal findings and improve the outcome in patients with chronic abdominal pain, as it allows surgeons to see and treat many abdominal conditions that cannot be diagnosed otherwise. Methods: A prospective longitudinal study was conducted from August 2016 to September 2017 in the Surgery Department of Vinayaka Missions Kirupananda Variyar Medical College, Salem. 50 patients with abdominal pain for 3 months and above were included in the study. Detailed history was recorded from patients and thorough clinical examination was performed. The findings were recorded in the proforma. Results: The most common laparoscopy finding among the study subjects was dense adhesions (26%) followed by abdominal TB (18%) and mesenteric lymphadenopathy (16%). 88% of the study subjects had a total relief of their abdominal pain and 6% of the patients felt that the pain was reduced and for the remaining 6% the pain was still persistent. Conclusions: The efficacy of diagnostic laparoscopy was 90% in the current study. Laparoscopy has an effective diagnostic role in evaluating patients with chronic abdominal pain, in whom conventional methods of investigations have failed to elicit a certain cause. The therapeutic value of diagnostic laparoscopy is also accepted, well-appreciated, and it cannot be underestimated.